Naposo Nauli Bulung Sebagai Pencegah Kejahatan Mutilasi Di Desa Barak Gajah - Cindy Fadilah Nasution; Luthfiyatul Adawiyah Siregar; Aziah Aulisa Putri; Dwi Silvia Zakiah Sarianta Siregar; Asnarni Lubis (LPPI UMN AL WASHLIYAH, 2024)
The increase in crime cases in society is a matter of great concern. This is because one of the causes of crime is due to a lack of knowledge in critical thinking which causes people, especially teenagers, to undervalue the importance of self awareness and care about the importance of protecting themselves from various crimes. This counseling aims to introduce teenagers in Barak Gajah village about the importance of protecting themselves and creating inclusive policies by building a Naposo Nauli Bulung Organization and adding insight into preventing and reducing all forms of crime by carrying out productive activities in order to strengthen how to prevent crime, especially the term mutilation, from happening. The method used in this implementation is the Participatory Action Research (PAR) method which is divided into several stages, namely in the first stage starting with giving a pre-test in the form of a questionnaire to measure the initial ability of the youth of the Barak Gajah Village related to crime, educational activities, watching activities together, recitation activities, and sports activities. The results showed that the average understanding of Barak Gajah Village youth increased from 40% to 90% after counseling. Thus, Naposo Nauli Bulung activities can be used as an effort to prevent crime among adolescents.